FAKTOR YANG BERHUBUNGAN DENGAN PERILAKU SEKS PRANIKAH PADA REMAJA KECAMATAN KEPULAUAN MASALOKA RAYA TAHUN 2022 - Irma Irma; Paridah Paridah; Yuni Yuni (FKM Universitas Halu Oleo, 2022)
Adolescence is a period of growth and development both physically, psychologically and intellectually. The characteristics of teenagers who have a great curiosity, like adventure and challenges and tend to dare to take risks without careful consideration. Premarital sexual behavior is a sexual activity that involves two people who like or love each other, which is carried out before marriage. This study aims to determine the factors associated with premarital sexual behavior in adolescents in the Masaloka Raya Islands sub-district in 2022. This study used analytical observation with a Cross Sectional Study approach. The population in this study were all teenagers in Kep. Masaloka Raya. The sample in the study was 174 people. Sample selection using total sampling technique. The results showed that there was a significant relationship between courtship status (p value = 0.000 < 0.05), peer influence (p value = 0.000 < 0.05) and premarital sex behavior, on the contrary there was no significant relationship between knowledge (p value = 0.356 > 0.05), parental role (p value = 0.079 > 0.05) with premarital sex behavior. The conclusion of this study is that the variables of courtship status and peer influence have a significant relationship with premarital sex behavior in adolescents, while knowledge and parental roles do not have a significant relationship with premarital sex behavior in adolescents in the Masaloka Raya Archipelago District in 2022.